Evaluation of a transcriptomic signature of tuberculosis risk in combination with an interferon gamma release assay: A diagnostic test accuracy study. (May 2022) - Mulenga, Humphrey; Fiore-Gartland, Andrew; Mendelsohn, Simon C.; Penn-Nicholson, Adam; Mbandi, Stanley Kimbung; Nemes, Elisa; Borate, Bhavesh; Musvosvi, Munyaradzi; Tameris, Michèle; Walzl, Gerhard; Naidoo, Kogieleum; Churchyard, Gavin; et al.
Summary: Background: We evaluated the diagnostic and prognostic performance of a transcriptomic signature of tuberculosis (TB) risk (RISK11) and QuantiFERON-TB Gold-plus (QFTPlus) as combination biomarkers of TB risk. Methods: Healthy South Africans who were HIV-negative aged 18–60 years with baseline RISK11 and QFTPlus results were evaluated in a prospective cohort study conducted between Sept 20, 2016 and Dec 20, 2019. Prevalence and incidence-rate ratios were used to evaluate risk of TB. Positive (LR+) and negative (LR–) likelihood ratios were used to compare individual tests versus Both-Positive (RISK11+/QFTPlus+) and Either-Positive (RISK11+ or QFTPlus+) combinations. Findings: Among 2912 participants, prevalent TB in RISK11+/QFTPlus+ participants was 13·3-fold (95% CI 4·2–42·7) higher than RISK11–/QFTPlus–; 2·4–fold (95% CI 1·2–4·8) higher than RISK11+/QFTPlus–; and 4·5-fold (95% CI 2·5–8·0) higher than RISK11–/QFTPlus+ participants. Risk of incident TB in RISK11+/QFTPlus+ participants was 8·3-fold (95% CI 2·5–27·0) higher than RISK11–/QFTPlus–; 2·5-fold (95% CI 1·0–6·6) higher than RISK11+/QFTPlus–; and 2·1-fold (95% CI 1·2–3·4) higher than RISK11–/QFTPlus+ participants, respectively. Compared to QFTPlus, the Both-Positive test combination increased diagnostic LR+ from 1·3 (95% CI 1·2–1·5) to 4·7 (95% CI 3·2–7·0), and prognostic LR+ from 1·4 (95% CI 1·2–1·5) to 2·8 (95% CI 1·5–5·1), but did not improve upon RISK11 alone. Compared with RISK11, the Either-Positive test combination decreased diagnostic LR– from 0·7 (95% CI 0·6–0·9) to 0·3 (95% CI 0·2–0·6), and prognostic LR– from 0·9 (95% CI 0·8–1·0) to 0·3 (0·1–0·7), but did not improve upon QFTPlus alone. Interpretation: Combining two tests such as RISK11 and QFTPlus, with discordant individual performance characteristics does not improve overall discriminatory performance, relative to the individual tests. Funding: Bill and Melinda Gates Foundation, South African Medical Research Council.